Quantitative selection of focal birds and mammals in higher‐tier risk assessment: An application to rice cultivations. (3rd November 2021) - Orioli, Valerio; Caffi, Alessandra; Marchetto, Flavio; Dondina, Olivia; Bani, Luciano
Abstract: European Pesticide Registration requires a risk assessment (RA) for nontarget organisms according to EU Regulation. European Authorities have developed Guidance Documents (GDs) for RA considering exposure scenarios for the required organisms typical for terrestrial crops. The "Birds and Mammals EFSA GD" allows using multiple sources of information to extract information on species frequency needed in identifying focal species for higher‐tier RA. We developed an analytical framework to calculate species frequency according to availability of species and habitat quantitative data. Since the exposure scenarios reported in the EFSA GD are inconsistent for rice, we tested the method on birds and mammals in a portion of the largest rice‐cultivated area of Europe, the Italian Po floodplain. We derived three lists of focal species: (a) an expert‐based list based on land‐use data only, which can be useful for a preliminary exploration of potential candidate species; (b) a list derived from the interpolation of species data only, which reflects actual species frequency in rice fields; and (c) a list obtained by a species distribution model based on species monitoring and land‐use data, which account for species selectivity for rice crops and are transferable to other contexts. Focal species were identified for crop‐specific diet‐foraging guilds, to build specific exposure scenarios to assess the risk from pesticides application in rice fields. The partial differences between our lists and those previously proposed highlight the need for identifying national lists, which can vary according to study area, biogeographic region and exposure scenarios. The application of the proposed method in European rice‐producing countries should lead to crop‐specific lists, which could then be integrated to obtain a flexible European list applicable to higher‐tier RA. Integr Environ Assess Manag 2022;18:1020–1034. © 2021 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC). Key Points: We provided an analytical framework for improving selection of focal species for higher‐tier risk assessment of pesticides in rice‐cultivations and any other crop. Expert‐based models should be used for preliminary exploration of focal species, spatial interpolation of species occurrences should be used for local assessment, while species distribution modelling provides information transferable to other contexts. We identified the Black‐winged Stilt and the Northern Lapwing as focal species for water insectivores, the Little Egret for water carnivores, the Moorhen for water herbivorous birds and the Barn swallow and the Northern House‐martin for aerial insectivorous birds. We identified the Eurasian harvest mouse as focal species for water insectivorous and herbivorous mammals, the Eurasian water shrew for water carnivorous and piscivorous mammals, and the Lesser horseshoe bat for aerial insectivorous mammals.